The harmonica - Johnston, Tony, 1942-; Mazellan, Ron (Watertown, MA : Charlesbridge, 2004)
Separated from his parents in Poland during World War II, a young Jewish boy enslaved in a concentration camp, keeps hope alive while playing Schubert on his harmonica whenever the camp's commandant orders him to play.
1 6 13 18 19 21 25 27 29
Keywords: Harmonica -- Juvenile fiction; Jews -- Juvenile fiction; Concentration camps -- Juvenile fiction; World War, 1939-1945 -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction